TRANSFORMING THE ROLE OF THE QADIRIYAH NAQSHBANDIYAH SURYALAYA ORDER IN RURAL SOCIAL SOLIDARITY - Toto Ahmad Sahid; Moh Ali (UIN Antasari Banjarmasin, 2025)
This study aims to analyze the role of the Tarekat Qadiriyah Naqsyabandiyah (TQN) Suryalaya in fostering social solidarity among the residents of Gunungmanik Village, Talaga District, Majalengka Regency. The background of this research arises from the phenomenon of weakening social bonds and moral values in rural communities as a consequence of modernization and the erosion of spiritual values. Within this context, TQN Suryalaya emerges as a Sufi movement that not only emphasizes the ritual aspects of dzikr (remembrance of God) but also performs a social function in strengthening community cohesion and the spirit of mutual cooperation (gotong royong) among villagers. This study employs a qualitative descriptive approach with a sociology of religion perspective. Data were collected through in-depth interviews, participatory observation, and documentation of the order’s activities. The key informants consisted of TQN teachers, local administrators, community leaders, and ordinary residents. The findings indicate that the practices of daily dzikr, Monday night khotaman, and monthly manaqiban play a vital role in reinforcing social relationships, nurturing empathy, and cultivating the spirit of mutual assistance within the community. Sufi values such as ikhlas (sincerity), tawadhu’ (humility), ta‘awun (mutual help), and ukhuwah (brotherhood) serve as the moral foundation that sustains social solidarity and communal harmony in the village.